RESULTS OF USTEKINUMAB TREATMENT IN PATIENTS WITH PSORIATIC ARTHRITIS IN THE RUSSIAN FEDERATION ACCORDING TO THE DATA OF PSUMMIT 1 AND PSUMMIT 2 - Yu. L. Korsakova; A. A. Godzenko; A. O. Pchelintseva; O. Yu. Grigoryeva; L. N. Denisov; E. L. Nasonov (Научно-практическая ревматология)
Psoriatic arthritis (PsA) is a chronic inflammatory disease of the joints, vertebral column,  and entesises, which is associated with psoriasis. T helper type 17 cells (Th-17)  play a leading role in the development of inflammation in psoriasis and PsA so different biologicals affecting interleukins (IL) 17 and 23 are being intensively investigated. Randomized, placebo-controlled Phase III PSUMMIT 1 (NCT01009086,  EudraCT  2009-012264-14) and PSUMMIT 2 (NCT01077362,  EudraCT  2009-012265-60) studies were undertaken  to evaluate the efficiency and tolerability of  ustekinumab  (UST) treatment in PsA patients.Subjects and methods. The PSUMMIT 1 study covered 152 Russian patients with active PsA (≥5 tender and ≥5 swollen joints; C-reactive protein ≥3 mg/l) who were randomly (using the dynamic centralized randomization method on the basis of an interactive vocal response algorithm) divided into three groups (at a 1:1:1 ratio): 1) subcutaneous UST 45 mg; 2) UST 90 mg; 3) placebo (PL) at baseline, 4 weeks later, and then every 12 weeks). After 16 weeks the patients showing a less than 5% reduction  in the number of tender and swollen joints were given UST 45 mg (if they belonged to the PL group) or 90 mg (if they were in the UST 45-mg group). The PL-receiving patients were given UST 45 mg at weeks 24 and 28 and then every 12 weeks. The treatment duration was 2 years. A therapeutic  response  was estimated by theAmericanCollege of Rheumatology (ACR) response criteria. The PSUMMIT 2 study enrolled 40 Russian patients who had previously received or were currently receiving disease-modifying anti-rheumatic drugs and/or nonsteroidal  anti-inflammatory drugs and tumor necrosis factor-α  inhibitors. The patients were randomized  to the groups of those receiving UST 45 mg or 90 mg or PL at baseline and at week 4, then once every 12 weeks. The last dose of UST was given at week 40. The follow-up lasted until week 60.Results and discussion. In the PSUMMIT 1 study, 24-week administration of UST 45 mg and 90 mg significantly more frequently ensured a 20% improvement according to the ACR criteria than that of PL (39.2; 44.0, and 15.7%, respectively; p < 0.01); the therapeutic response persisted until week52. In the PSUMMIT 2, following 24 weeks, the UST 45-mg and 90-mg groups considerably more often showed a 20% improvement according to the ACR criteria than the PL group (64.3, 57.1, and 16.7%, respectively; p < 0.01); the therapeutic response persisted until week 52. Among 150 Russian patients taking UST, on the average, for 45.1 weeks in the PSUMMIT 1 study, 62 (41.3%) were observed to have adverse events (AE) that were serious in 6 (4.0%). Among 40 PsA patients who participated  in the PSUMMIT 2 study inRussia, AEs were seen in a total of 25 (62.5%) patients, serious AEs being absent.Conclusion. The results of the PSUMMIT 1 and PSUMMIT studies in the Russian population  indicated that UST treatment contributed  to a significant reduction  of PS symptoms and exhibited a good tolerability.DOI: http://dx.doi.org/10.14412/1995-4484-2015-125-133